Founder Turnover in Venture Capital Backed Start-Up Companies - Heibel, Martin (Springer, 2017)
Rapid firm growth fueled by venture capital investments triggers tremendous dynamics in the development of young firms. However, entrepreneurship research frequently ascribes a rather static role to the entrepreneur in his start-up company. The phenomenon of founder turnover – a situation in which entrepreneurs decide to leave their initial job position – has mostly been ne¬glected. Moreover, little is known about the frequency, causes, and the impact of founder turnover.